Analisa Scanning Electron Microscope Komposit Polyester Dengan Filler Karbon Aktif dan Karbon non Aktif - Farikhin, Fahrizal, Ir. Ngafwan, MT, Joko Sedyono, ST, M.Eng, Ph.D (2016)
This research is aimed to determine the relationship of the volume fraction and weight fraction of carbon theoretically and morphological structure of polyester composites with carbon filler active and non-active carbon with SEM method. The manufacture of composites using variations of weight fraction carbon micro filler 1%, 3% and 6% with polyester resin Yukalac 157 BQTN - EX. Mixing process carbon particles with resin using methods stirring with a maximum rotation speed of 2200 rpm for 10 min for activated carbon and 7 minutes for the non-active carbon. SEM analysis use 1.500x magnification 1.500x.. Based on the SEM images, it can be observed the value of the volume fraction of carbon. The average value obtained volume fraction of activated carbon to the weight fraction of 1% at 28.49%, the weight fraction of 3% at 27.38%, and 6% weight fractions of 24.87%. For non-active carbon filler obtained average value of the volume fraction of the weight fraction of 1% at 29.47%, the weight fraction of 3% at 31.89%, and 6% weight fractions of 36.54%. In composites with activated carbon filler, the greater the weight fractions, the smaller the volume fraction values. These results are inversely proportional to the carbon composite with a non-active filler, the greater the weight fractions then increases the value of the volume fraction. The decline in the value of the volume fraction of the activated carbon is probably caused due to the reaction between the activated carbon with polyester resin in the mixing process, because there is an increase in temperature. Morphology composites with carbon filler actively demonstrate carbon particles bind to each other thus leading to the formation of the fiber. These results are most clearly seen in the heavy fraction of 3%. While in composites with carbon filler non-active carbon particles to form agglomerates of particles. These results are most clearly seen in the heavy fraction 6%.